Komponen Bioaktif pada Madu Karet (Hevea brasiliensis) Madu Kaliandra (Calliandra callothyrsus) dan Madu Randu (Ceiba pentandra) - Ustadi Ustadi; Lilik Eka Radiati; Imam Thohari (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2017)
The objectives of this study were to determine of bioactive compoounds from the different plants such as kapok, calliandra and rubber. The samples were obtained from Kediri (Calliandra), Sragen (Rubber) and Pasuruan (Kapok). The results showed the different of bioactive compounds. It had the following phenolic content ranged from 309.12 ± 33.40 mg/GAE kg (Kapok honey) to 557.93 ± 13.41 mg/GAE kg (Calliandra honey), flavonoid content ranged from 47.25 ± 1.49 mg QE/100 g (Kapok honey) to 156.27 ± 5.69 mg/GAE kg (Calliandra honey), vitamin C content ranged from 25.47 ± 1.62 mg/100 g (Kapok honey) to 31.04 ± 1.45 mg/100 g (Calliandra honey). The IC50 of Calliandra honey (3.36 ± 0.89 mg/mL) showed that antioxindat activity is higher than Rubber and Kapok honey (15.08  ± 1.49 mg/mL and 16.83 ± 1.23 mg/mL, respectively).